M-learning applied to primary school at the “Liceo Técnico Superior” of Popayán - Betancourt Silva, Juan Camilo; Obando Chamorro, Jehovanny José; Burbano González, Clara Lucía; Márceles Villalba, Katerine; Carrasco Saenz, José Luis (I+ T+ C- Research, Technology and Science, 2017)
In today’s society, with the rise of ICT and the accelerated growth of technological resources; mobile devices have taken an important role in the daily life of the human being, in this sense, Castells [1] argues that the “advent of mobile technologies involves a series of questions about the effects of generalization in technologies for everyday life, posing how they influence family, work, and education; demanding the constant change, adaptability and flexibility in the handling of “smartphones”, being help in the educational field; Under mobile learning, it is possible to obtain: portability, connectivity, ubiquity and permanence, giving a step to the use of mobile technologies as a basis in the learning process, leading the individual to permanent online learning, acquiring new knowledge and adapting them to generate competences technologies that allow the following question to be asked: should the use of the Smartphone be prohibited in classrooms? In this sense, the project of technological articulation in the area of education is structured to improve cognitive and technological competences in the IT subject of the Liceo Técnico Superior Educational Institution, where it is evident that first grade teachers lack knowledge in the appropriation of technological resources such as m-learning, causing a gap in the use of pedagogical and didactic resources in the use of mobile devices, being necessary the implementation of tools techno-pedagogical endeavors as Socrative under m-learning methodologies that contribute to the improvement of activities in synchronous and asynchronous time, to generate critical thinking in the learning process.